Past and recent effects of livestock activity on the genetic diversity and population structure of native guanaco populations of arid patagonia - Mesas, Andrés (2021)
Extensive livestock production and urbanization entail modifications of natural landscapes, including installation of fences, development of agriculture, urbanization of natural areas, and construction of roads and infrastructure that, together, impact native fauna. Here, we evaluate the diversity and genetic structure of endemic guanacos (Lama guanicoe) of the Monte and Patagonian Steppe of central Argentina, which have been reduced and displaced by sheep ranching and other impacts of human activities. Analyses of genetic variation of microsatellite loci and d-loop revealed high levels of genetic variation and latitudinal segregation of mitochondrial haplotypes. There were indications of at least two historical populations in the Monte and the Patagonian Steppe based on shared haplotypes and shared demographic history among localities. Currently, guanacos are structured into three groups that were probably reconnected relatively recently, possibly facilitated by a reduction of sheep and livestock in recent decades and a recovery of the guanaco populations. These results provide evidence of the genetic effects of livestock activity and urbanization on wild herbivore populations, which were possibly exacerbated by an arid environment with limited productive areas. The results highlight the importance of enacting conservation management plans to ensure the persistence of ancestral and ecologically functional populations of guanacos.